Appraising Protected Area Management Planning in Nepal - Poudel, Buddi Sagar (The Initiation, 2011)
This paper distils Nepal's experience on protected area management planning, with particular reference to implementation of management plan. It also reviews the status of PA management plan and legal provisions related to management plan. Management plan is the road map to guide conservation efforts and sets out the desired future of protected area. Five-year management plan of protected areas have been prepared and implemented. Although park management plans were formulated for most of the parks and reserves, there remained wide gaps during its timely and effective implementation. The aim of this paper is to answer the question "what are the issues in management planning process and implementation". Building on the strength of the past and keeping the existing weaknesses in mind, the management effectiveness should be evaluated and improved. DOI: http://dx.doi.org/10.3126/init.v4i0.5538 The Initiation Vol.4 2011 69-81